Strategi Meningkatkan Pelayanan Investasi yang Kondusif dan Ramah Pasar di Era Otonomi Daerah - Erika Revida (Jurnal Transformasi Administrasi, 2018)
Increasing investment in the local area is a fundamental issue and the fore today. This is not on ly to improve the local economy, but also improve the competitiveness of local economy and so ciety incomes. Therefore, it needs a lot of strategy. There are a lot of strategy to improve the con dusive and market friendly investment services. That are by improving the quality ofhuman resources (HR), the institutional factor, reforming the regulation of investment, transparency and accountabilit, safety factor, complaint management system, giving incentives for in vestors and applying Rewards and Punishment methods.